2016
DOI: 10.1186/s13075-016-0997-y
|View full text |Cite
|
Sign up to set email alerts
|

E2 regulates MMP-13 via targeting miR-140 in IL-1β-induced extracellular matrix degradation in human chondrocytes

Abstract: BackgroundEstrogen deficiency is closely related to the development of menopausal arthritis. Estrogen replacement therapy (ERT) shows a protective effect against the osteoarthritis. However, the underlying mechanism of this protective effect is unknown. This study aimed to determine the role of miR-140 in the estrogen-dependent regulation of MMP-13 in human chondrocytes.MethodsPrimary human articular chondrocytes were obtained from female OA patients undergoing knee replacement surgery. Normal articular chondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 40 publications
2
53
0
1
Order By: Relevance
“…74 Interestingly, when miR-140 was over-expressed in Col2a1-expressing cells, these mice appeared to be somewhat protected from proteoglycan and type II collagen loss following antigen-induced arthritis (AIA), an arthritic injury model that results in severe inflammation within the synovial joint. These findings, together with other reports that miR-140 has anti-catabolic or pro-anabolic effects in chondrocytes [74][75][76][77][78][79] suggests that targeting this miRNA could be a promising therapeutic approach to treat inflammation-induced cartilage degradation. Interestingly, a recent study showed that exosomes derived from rat synovial mesenchymal stem cells (SMSCs) and engineered to over-express miR-140 (SMSC-140-Exos) are chondroprotective.…”
Section: Mirnas Regulating Skeletal Development and Homeostasis-evidesupporting
confidence: 67%
“…74 Interestingly, when miR-140 was over-expressed in Col2a1-expressing cells, these mice appeared to be somewhat protected from proteoglycan and type II collagen loss following antigen-induced arthritis (AIA), an arthritic injury model that results in severe inflammation within the synovial joint. These findings, together with other reports that miR-140 has anti-catabolic or pro-anabolic effects in chondrocytes [74][75][76][77][78][79] suggests that targeting this miRNA could be a promising therapeutic approach to treat inflammation-induced cartilage degradation. Interestingly, a recent study showed that exosomes derived from rat synovial mesenchymal stem cells (SMSCs) and engineered to over-express miR-140 (SMSC-140-Exos) are chondroprotective.…”
Section: Mirnas Regulating Skeletal Development and Homeostasis-evidesupporting
confidence: 67%
“…In addition to bone-inducing effects, estrogen sustains normal chondrocyte metabolism and reduces the sensitization of articular cartilage to OA pathogenic factors [20]. Thus, we suggest that Rg1 may exert estrogen-like effects in OA treatment.…”
Section: Discussionmentioning
confidence: 91%
“…MMP-13 plays a pivotal role in initiating the degradation of type II collagen [20]. Previous studies have shown that herbs can decrease MMP-13 expression, when administered as complementary OA treatment [7,21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-140-5p gained a lot of attention for playing dual roles in both cartilage homeostasis and development 36, 37 by targeting RalA to enhance SOX9 and aggrecan (ACAN) 38 and showing potential for preventing OA 39, 40.…”
Section: Introductionmentioning
confidence: 99%